PJMHS 2022
DOI: 10.53350/pjmhs20221612122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inspiratory Muscles Trainer in Pulmonary Rehabilitation Program among COPD Patients

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is associated with prolonged respiratory problems and compromised airflow. Eventually, routine activities become troublesome. Pulmonary rehabilitation program and specific training of inspiratory muscles can do management of such patients. Aim: To find out the effects of Inspiratory Muscle Trainer on dyspnea in moderate COPD patients during Pulmonary Rehabilitation in terms of improvement of pulmonary lung function and Multidimensional Dyspnea profile. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Furthermore, comprehensive treatment strategies, such as medication, rehabilitation plans, and respiratory support, may play a more crucial role in improving COPD patients' lung function. One of the included studies in this meta-analysis indicated that RMT combined with PR had a better effect on FEV 1 /FVC compared to PR alone [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, comprehensive treatment strategies, such as medication, rehabilitation plans, and respiratory support, may play a more crucial role in improving COPD patients' lung function. One of the included studies in this meta-analysis indicated that RMT combined with PR had a better effect on FEV 1 /FVC compared to PR alone [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Study selection was independently assessed by 2 researchers using the eligibility criteria, and the differences were resolved through consult with the third researcher. Relevant data were extracted from the selected studies, including name of first author, year of publication, country, study design, groups with sample sizes, evaluation time, number and percentage of males, mean age, and baseline forced expiratory volume in 1 s to forced vital capacity ratio (FEV 1 /FVC) [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] ]. The risk of bias was assessed using the Cochrane Collaboration tool [ 22 ].…”
Section: Methodsmentioning
confidence: 99%